INSIGHTS INTO INTRA-PARTY DECISION-MAKING IN LATVIA’S POLITICAL PARTIES - Ilze Balcere (Baltic Journal of Political Science, 2018)
This article examines the decision–making processes within political parties in Latvia. Two important variables have been chosen for analysis: 1) policy formulation (which actors are involved in the elaboration of election programs), and 2) candidate selection (how parties create their electoral lists). A survey of Saeima (Latvia’s parliamentary body) deputies indicates that party board members have the most say in deciding which individuals to include on electoral lists and which policies to pursue; financial supporters seem to have almost no impact on parties’ internal decision-making processes.